2022
DOI: 10.1111/os.13380
|View full text |Cite
|
Sign up to set email alerts
|

Relook into the Risk Factors of Proximal Junctional Kyphosis in Early Onset Scoliosis Patients: Does the Location of Upper Instrumented Vertebra in Relation to the Sagittal Apex Matter?

Abstract: Objective Growing rods surgery is the mainstay of treatment for early‐onset scoliosis (EOS) while proximal junctional kyphosis (PJK) is one of the most commonly reported postoperative complications. We sought to investigate the impact of the location of upper instrumented vertebra (UIV) in relation to the sagittal apex on proximal junctional kyphosis in EOS after traditional growing rods (GRs) treatment. Methods A total of 102 EOS patients who received traditional growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A younger age at the time of the index surgery and longer procedure times have also been shown to be associated with the incidence of PJK [ 20 ]. In this study, the rate of PJK was 54.2% (19 of 35 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A younger age at the time of the index surgery and longer procedure times have also been shown to be associated with the incidence of PJK [ 20 ]. In this study, the rate of PJK was 54.2% (19 of 35 patients).…”
Section: Discussionmentioning
confidence: 99%
“…PJK is a common alignment-related complication in patients with EOS undergoing TGR [15,16], and an incidence rate of 12%-56% has been reported in previous studies [17][18][19]. The difference rate of PJK in various studies has been attributed to differences in the study sample, EOS etiology, surgical procedure, fixation instrumentation, and follow-up period [17,20,21]. Several risk factors have also been reported for PJK, including the location of the upper or lower instrumented vertebra, proximal thoracic scoliosis of >40°, a main thoracic kyphosis of >60°, a higher correction rate, and location of the UIV in relation to the sagittal apex [17,18,20,[22][23][24].…”
Section: A B C Dmentioning
confidence: 99%
“…This is a common finding in spine surgery in the elderly [ 8 ], especially when the sagittal balance is overestimated, or the proximal instrumentation level is not adequate. It is also a known complication in severely involved paralytic patients with poor muscle tone, if the upper instrumented vertebra is short of the apex of the thoracic kyphosis [ 9 , 10 ].The current report relates to a pediatric but severely involved CP patient. However, like in almost all patients in this category, posterior instrumentation extended proximally to T2 in an attempt to decrease the risk of PJK.…”
Section: Discussionmentioning
confidence: 99%
“…Miladi et al found fewer mechanical complications with fusionless double ends technique using hooks instead of transpedicular screws for proximal fixation in a growth-friendly scoliosis surgery [ 29 ]. Other factors that can affect the success rates of treatment include the severity of the condition, the age of the patient, and the presence of any underlying conditions especially in neuromuscular origin [ 28 , 31 ] Further research is needed to determine the success rates of different treatment options for proximal junctional problems in EOS.…”
Section: Discussionmentioning
confidence: 99%